Quality Control Of Crude Drugs And Capsules Of Turmeric (Curcuma longa L.) - Dwi Hartanti; Jirapat Theeravit (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2018)
Turmeric (Curcuma longa L.) is a medicinal plant commonly used in Thai Traditional Medicine (TTM), both in single use and formula. It has been known for its antioxidant activity and applied for management of many diseases. In this article, we reported some aspects of quality control of crude drugs and capsules of turmeric according to the standards set in Thai Herbal Pharmacopeia (THP). The results of our evaluations demonstrated that turmeric crude drugs met the criteria set in THP for microscopical identification, foreign matter (1.31%), loss on drying (6.89±0.174%), ethanol-soluble extractive (13.56%), water-soluble extractive (15.17%), and the profile of Thin Layer Chromatography (TLC) chromatogram. However, its volatile oil content (5.95%) was below the minimum value set in THP. The turmeric capsules met the criteria set in THP for loss on drying (8.64±0.093%), ethanol-soluble extractive (18.07%), water-soluble extractive (14.95%), and profile of TLC chromatogram.